THE ROLE OF FATHER IN CHILD CARE IN THE RURAL FAMILY: PROVISION OF MATERIAL NEEDS - Bartosiak, Lukash (The Modern Higher Education Review, 2017)
The article is part of the research project “Parental relations in rural areas”. The article focuses on a small fragment of the project related to the role of the father in the process of a child’s upbringing. The activities related to the organization of living conditions can be classified as the criteria for determining the participation of parents in childcare. A qualitative analysis of the collected research materials, preceding the theoretical introduction, provides modern knowledge on caring for the child, father’s participation in the protection of children’s health, cooking for the child, material support for children.